Quantum key distribution using the localized soliton pulses via a wavelength router in the optical network - Pornsuwancharoen, N.; Dunmeekaew, U.; Yupapin, P. P. (My University, 2010)
We propose a new system of a continuous variable quantum key distribution via a wavelength router in the optical networks. A large bandwidth signal is generated by a soliton pulse propagating within the micro ring resonator, which is allowed to form the continuous wavelength with large tunable channel capacity. There are two forms of localized soliton pulses proposed. Firstly, the required information is transmitted via the localized temporal soliton pulse. Secondly, the continuous variable quantum key distribution is formed by using the localized spatial soliton pulse via a quantum router and networks, which is formed by using and optical add/drop multiplexer incorporating in the network. The localized soliton pulses are available for add/drop signals to/from the optical network, where the high security and capacity information can be performed. © 2009 Elsevier GmbH. All rights reserved.
Keywords: Continuous variable; Perfect security; QKD; Quantum network; Quantum router